Clonal mapping of the human aorta. Relationship of monoclonal characteristics, lesion thickness, and age in normal intima and atherosclerotic lesions. - Pearson, T. A. (1987)
The surfaces of 8 aortas from women heterozygous for G-6-PD isoenzymes were mapped for an examination of the relationships of monoclonality, lesion type, lesion thickness, and age of the patient. The percent B isoenzyme value of samples of normal intima (n = 315), fatty steak (n = 68), or fibrous plaque (n = 64) was used to define monoclonality, expressed as the [Z] score, the number of standard deviations from the mean percent B isoenzyme of samples of underlying media. Intimal thickness increased significantly with type of lesion, such that intima less than fatty streak less than fibrous plaque, and with the age of the patient. The percentage of monoclonal portions also increased with lesion type, such that 1% of samples of normal intima were monoclonal, compared with 4.4% of fatty streaks and 12.5% of fibrous plaques (P less than 0.005). Monoclonality increased with intimal thickness when normal intima, fatty streaks, and fibrous plaques were combined (P = 0.0001). When examined separately, normal intima showed a direct correlation between monoclonality and intimal thickness. In contrast, the monoclonality of fatty streaks was inversely associated with thickness (P = 0.016) and the monoclonality of fibrous plaques not related to thickness. When entered into a multiple regression model, lesion type and age, but not lesion thickness, significantly predicted monoclonality. The lack of association of intimal thickness with monoclonality suggests that it is the type of lesion that determines monoclonality and not merely its thickness. This implies that mechanisms other than clonal selection are responsible for the monoclonal characteristics of human atherosclerotic lesions.